IGFBP7 downregulation or overexpression effect on bovine preadipocyte differentiation. Issue 1 (1st February 2021) - Hu, Zhongchang; Wu, Jian; Qin, Lihong; Jin, Haiguo; Cao, Yang; Zhao, Yumin
Abstract: The insulin-like growth factor binding-protein 7 (IGFBP7) has binding affinities to IGFs and is able to either positively or negatively regulate the IGFs signaling pathway. It also plays a crucial role in cell growth, differentiation and development in an IGF-independent manner. Herein, we investigated the specific regulation of the gene encoding for IGFBP7during the differentiation process of the adipocyte cells of the Yan Yellow Cattle by interfering with or by overexpressing the IGFBP7 gene. As a result, we found that the mRNA expression levels of IGFBP7 were significantly increased during the formation of progenitor cells. In addition, the expression levels of the lipoprotein lipase (LPL) and transcription factors (PPARγ, C/EBPα) were also significantly increased. IGFBP7 gene overexpression and RNA interfering promoted and inhibited respectively the lipid accumulation and triglyceride production in mature adipocytes, and the expression of the LPL and transcription factors (PPARγ, C/EBPα). The changes in the protein expression levels of IGFBP7 and adipogenic factors were in accord with the changes observed in the mRNA levels. In conclusion, our results indicate that IGFBP7 plays an important regulatory role in the differentiation of preadipocyte cells.